The Study of Relationship among Experiential Marketing, Service Quality, Customer Satisfaction, and Customer Loyalty - Zena, Puti Ara; Hadisumarto, Aswin Dewanto (UI Scholars Hub, 2021)
Experiential marketing is one of the marketing approaches that gives a great framework to combine experience and entertainment elements into a product or service. Some of businesses in Indonesia have already used this approach and one of them is Strawberry Cafe which provides many kinds of free board games for the customer. The purpose of this research is to understand the impact of experiential marketing used by Strawberry Cafe related to customer satisfaction and loyalty. The data were collected from 142 respondents but after screening, only 80 that met the requirements and could be analyzed. Structural Equation Modeling (SEM) using LISREL software was used to analyze the data. This research found that itexperiential marketing used by Strawberry Cafe can affect customer loyalty.